2003
DOI: 10.1038/sj.gene.6363954
|View full text |Cite
|
Sign up to set email alerts
|

Novel genetic variation of human interleukin-21 receptor is associated with elevated IgE levels in females

Abstract: The interleukin-21 receptor (IL21R) was recently discovered as a novel member of the class-I-cytokine-receptor family and is selectively expressed in lymphoid tissues. IL21R shows strong sequence homologies to the interleukin-4 receptor a chain gene (IL4RA). In addition, both genes are adjacent and share structural similarity. We analyzed all the exons of the human IL21R gene and its 5 0 flanking region for sequence variation. We identified four novel single nucleotide polymorphisms (SNPs) and genotyped 300 he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 18 publications
(20 reference statements)
1
20
2
Order By: Relevance
“…These results indicate that polyclonal stimulation of B cells through CD40, although of physiologic relevance, delivers a strong polyclonal activation signal that, because of its intensity, is likely to mask the potential inhibitory effects of IL- 21 The results presented in this study indicate that healthy, as well as atopic, individuals respond with a differential sensitivity to the modulatory effects of IL-21 on the synthesis of IgE. Moreover, this differential sensitivity was found to be associated with the presence of a polymorphism in the gene encoding the IL-21R, which is the consequence of a nucleotide substitution in the 5Ј flanking region of exon 1B (T-83C) (14). We focused on this polymorphism, because among the four IL-21R gene variants that were reported in the literature, only the presence of the T-83C variant was found to be associated with enhanced IgE serum levels in healthy and, to a greater extent, in atopic individuals (14).…”
Section: Cd27mentioning
confidence: 78%
See 3 more Smart Citations
“…These results indicate that polyclonal stimulation of B cells through CD40, although of physiologic relevance, delivers a strong polyclonal activation signal that, because of its intensity, is likely to mask the potential inhibitory effects of IL- 21 The results presented in this study indicate that healthy, as well as atopic, individuals respond with a differential sensitivity to the modulatory effects of IL-21 on the synthesis of IgE. Moreover, this differential sensitivity was found to be associated with the presence of a polymorphism in the gene encoding the IL-21R, which is the consequence of a nucleotide substitution in the 5Ј flanking region of exon 1B (T-83C) (14). We focused on this polymorphism, because among the four IL-21R gene variants that were reported in the literature, only the presence of the T-83C variant was found to be associated with enhanced IgE serum levels in healthy and, to a greater extent, in atopic individuals (14).…”
Section: Cd27mentioning
confidence: 78%
“…Moreover, in a different study, injection of IL-21 into mice was found to inhibit Ag-specific IgE, but not IgG2a, responses and this effect was reportedly due to the inhibition of IL-4-induced germline C transcription by IL-21 (13). Recently, an association between a single nucleotide polymorphism (T-83C) in the IL-21R and the presence of elevated IgE serum levels has been reported (14), suggesting a negative regulatory function of IL-21 in the production of this istoype in humans as well.…”
Section: Ifn-␥-mediated Inhibition Of Human Ige Synthesis By Il-21 Ismentioning
confidence: 99%
See 2 more Smart Citations
“…Skewing of the balance between IL-4 and IL-21 signals could etiologically be associated with allergic hypersensitivities. Hecker et al (49) analyzed genetic polymorphisms in the human IL-21R gene and found that the presence of the T-83C variant was associated with elevated IgE serum levels in healthy and, to a greater extent, in atopic female individuals. Supplementation of the IL-21 signal may be a reasonable strategy to correct Id2 expression and in turn alleviate allergic symptoms in allergic patients.…”
Section: Discussionmentioning
confidence: 99%